Molecular detection of Mycoplasma gallisepticum by real time PCR - Farhana Yasmin,; Ideris, Aini; Omar, Abdul Rahman; Bejo, Mohd Hair; Tan, Sheau Wei; Tan, C. G.; Islam, R.; Ahmad, K. (Veterinary Association Malaysia, 2014)
Mycoplasma gallisepticum (MG) causes chronic respiratory disease leading to huge economic losses to the poultry industry worldwide. Early and efficient detection is therefore crucial in reducing the loss sustained by poultry farmers and poultry industry at large. Three main approaches are used for the diagnosis of MG: isolation and identification, serology and molecular detection method. Recently, real time polymerase chain reaction has been developed for the detection of infectious organisms, but so far only a limited number of diagnostic real time PCRs have been proposed for MG. This study was carried out to develop a SYBR green real time PCR assay for the detection of MG using primer set specific to the gapA gene. The primer set was able to amplify the expected DNA fragment of 505 bp. The assay was found to be specific and highly sensitive in detecting MG as indicated by its ability to detect between 260 ng/μl to 26 pg/μl DNA template. In conclusion, this study successfully developed a specific and sensitive real time PCR assay for the rapid detection of MG compared to conventional PCR method. Although the cost to carry out real time PCR is more expensive, it is a more specific, sensitive, and rapid method for detection of MG as compared with conventional PCR.